Effect of Ascorbic Acid to Recovery of Partial Tapping Panel Dryness (TPD) of Rubber Plant In The clones of PB 260 and IRR of 42 - Nurhadi Satrio; Rosmayati Rosmayati; E. Harso Kardhinata; Radite Tistama; Ade Fipriani (Jurnal Agroekoteknologi, 2016)
Effect of Ascorbic Acid to Recovery of Partial Tapping Panel Dryness (TPD) of Rubber Plant In The clones of PB 260 andIRR of 42,This aim of the research is to determine the effect of Ascorbic Acid to Recovery of Partial Tapping Panel Dryness (TPD) of clones PB 260 and IRR 42 rabber plant. This research was conducted at the research Estate and Physiological Laboratory of Balai Penelitian Sungei Putih, Pusat Penelitian Karet, Galang, Deli Serdang, Sumatra Utara, from May 2015 - October 2015, The research was designed by split plot with two factors. The main plot was clonesrubber plant (PB 260 and IRR 42), the subplot was treatments ascorbic acid(0 ppm, 150 ppm, 300 ppm, 450 ppm).Parameters measured were the levels of sucrose, inorganic phosphate, thiol, superoksidase dismutase (SOD), latex productivity and stoppage index.The results showed that clones PB 260 and IRR 42 rubber live significant different on production of latex. Application of Ascorbic acid him no significantly different on the levels of thiol, level of sukrosa,level of inorganic phosphate. The Interaction of the two treatment is significantly different with latex  productivity.